Additive Effects of Obesity on Myocardial Microcirculation and Left Ventricular Deformation in Essential Hypertension: A Contrast-Enhanced Cardiac Magnetic Resonance Imaging Study - Han, Pei-Lun; Li, Xue-Ming; Jiang, Li; Yan, Wei-Feng; Guo, Ying-Kun; Li, Yuan; Li, Kang; Yang, Zhi-Gang (Frontiers in Cardiovascular Medicine, 2022)
Objective The combination of hypertension and obesity is a major cause of cardiovascular risk, and microvascular changes and subclinical dysfunction should be considered to illustrate the underlying mechanisms and early identification, thereby developing targeted therapies. This study aims to explore the effect of obesity on myocardial microcirculation and left ventricular (LV) deformation in hypertensive patients by cardiac magnetic resonance (CMR). Methods This study comprised 101 hypertensive patients, including 54 subjects with a body mass index (BMI) of 18.5–24.9 kg/m2 and 47 subjects with a BMI ≥25 kg/m2, as well as 55 age- and sex-matched controls with a BMI of 18.5–24.9 kg/m2. Myocardial perfusion indicators [upslope, time to maximum signal intensity (TTM), maximum signal intensity (Max SI)] and LV strains [radial, circumferential, and longitudinal global peak strain (PS), peak systolic strain rate (PSSR), and peak diastolic strain rate (PDSR)] were measured. Results Upslope was numerically increased in obese patients but statistically decreased in non-obese patients compared with controls. Longitudinal PS deteriorated significantly and gradually from controls to non-obese and obese hypertensive patients. Longitudinal PSSR and PDSR were significantly decreased in obese hypertensive patients compared with the other two groups. BMI was associated with upslope (β = −0.136, P < 0.001), Max SI (β = −0.922, P < 0.001), longitudinal PSSR (β = 0.018, P < 0.001), and PDSR (β = −0.024, P = 0.001). Myocardial perfusion was independently associated with longitudinal PSSR (TTM: β = 0.003, P = 0.017) and longitudinal PDSR (upslope: β = 0.067, P = 0.020) in hypertension. Conclusion Obesity had adverse effects on microvascular changes and subclinical LV dysfunction in hypertension, and BMI was independently associated with both myocardial perfusion and LV deformation. Impaired myocardial perfusion was independently associated with subclinical LV dysfunction in hypertension.